2018
DOI: 10.1590/0034-7167-2016-0546
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with experience of intrafamilial violence by teenagers in school

Abstract: Regular use of condom and consumption of alcohol and/or marijuana represent risk behaviors to the experience of intrafamilial violence by teenagers in school, especially older than 15 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…However, there was a higher frequency of violent behavior against children and adolescents, compared to violence between adults or couples. Such results are in line with the literature, insofar as intrafamily violence is related to the imbalance of manifested power in the relationships between family members (Mota et al, 2018); children and adolescents are the most affected, as they are more physically and emotionally vulnerable (Maia et al, 2017). However, as previously mentioned, the violence practiced by figures of authority that are so significant for the child or adolescent, such as parents or caregivers, who must be responsible for embracing and protecting them, can cause several problems, whether physical, psychological, or even social (Lourenço et al, 2011;Reis et al, 2018;Zambrano-Villalba, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, there was a higher frequency of violent behavior against children and adolescents, compared to violence between adults or couples. Such results are in line with the literature, insofar as intrafamily violence is related to the imbalance of manifested power in the relationships between family members (Mota et al, 2018); children and adolescents are the most affected, as they are more physically and emotionally vulnerable (Maia et al, 2017). However, as previously mentioned, the violence practiced by figures of authority that are so significant for the child or adolescent, such as parents or caregivers, who must be responsible for embracing and protecting them, can cause several problems, whether physical, psychological, or even social (Lourenço et al, 2011;Reis et al, 2018;Zambrano-Villalba, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…However, among the violent behaviors most mentioned by these children/adolescents are those related to psychological violence, more specifically verbal violence, and control behaviors. The literature points out that, frequently, children and adolescents have been victims of psychological aggressions in the family environment, which involves behaviors such as yelling, insulting, humiliating, and threatening (Mota et al, 2018;Rocha & Moraes, 2011;Sani, 2003, Silva & Gonçalves, 2019. In addition, these authors emphasize that such behaviors are used daily as an education strategy, being considered extremely common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A violência intrafamiliar (física e/ou psicológica) é, da mesma forma, um fator de forte influência, além de ser um problema complexo e delicado que afeta milhões de famílias em todo o mundo, com graves consequências especialmente para crianças e adolescentes (Bickmore et al,2020). Corroborando com esses dados, Mota et al (2018) afirmam que os jovens têm maior chance de desenvolver problemas de saúde mental e comportamentais, como o uso de drogas e a condução de risco. Ademais, podem ser expostos a uma variedade de tipos de violência, incluindo agressão física, emocional e sexual, tanto sendo agredidos quanto testemunhando a violência dirigida a outros membros da família (Kitzmann et al, 2020).…”
Section: Resultsunclassified
“…3 These cases commonly occur in the home setting, as indicated by a Brazilian research conducted in a public school with 239 students, whose report of intrafamily violence was present in 60.7% of the adolescents. 4 A study that analyzed data from 171 countries also confirmed that the main perpetrators of this type of violence are the family members. 5 Considering that the family is the primary institution with the duty to protect and care for children and adolescents, experiencing domestic violence, especially by their legal guardians, is a paradox.…”
Section: Introductionmentioning
confidence: 93%